Estimation of Broadband Time-Interleaved ADC’s Impairments and Performance Using Only Single-Tone Measurements - Hong Zhang; Ahmad Hassan; Paul Chen; W. Martin Snelgrove; Anthony Chan Carusone (IEEE Access, 2022)
This paper presents a method to estimate the internal impairment parameters of broadband time-interleaved (TI) ADCs using only single-tone measurement data acquired at two different frequencies. The estimated parameters, which include the signal-independent noise power, clock jitter, nonlinearity coefficients, and all sub-ADC mismatch parameters, are further used to predict the error power breakdown and the overall SNDR of the ADC for a multi-tone signal. In this way, the underlying sources of a TI ADC’s performance limitations can be separately evaluated with standard and low-cost single-tone measurements. Accurate estimation of the ADC’s impairment parameters is helpful for iteratively improving the ADC’s performance during design, characterizing prototypes, and potentially simplifying the production test. The proposed method is verified with comprehensive simulations and hardware measurement on a 3.6-GSPS, 12-bit, 2-channel TI ADC whose SNDR for a multi-tone signal is estimated at about 1 dB of its actual value sweeping its internal parameters over a wide range of values.